Determinación de la calidad microbiológica del agua de consumo humano, para la implementación de un purificador solar en una vivienda del barrio La Merced, provincia de pichincha, periodo 2014-2015 - Cruz Nieto, Ana Gabriela (2015)
The microbiological quality affectation of human consumption water is influenced by natural and anthropogenic factors, which is reflected in the rivers, lakes and aquifers pollution that are a source of supply. This research was effectuated in two phases whose analyzes were sent to the ECU Microbiology Laboratory: in Phase Nº 1 was determined the water microbiological quality for human consumption of La Merced neighbourhood, where was obtained 9.3 x 104 cfu/100 ml of Total Coliform belongings to water collection tank, and 4.3 x 104 cfu/100 ml of Total Coliforms belonging to water of tap, the results do not comply with the standard INEN 1108: 2011. Phase Nº 2….